Numerical modelling of effect of baffle orientation offset on shell-and-tube heat exchanger performance (2018)
The performance of a shell-and-tube heat exchanger (STHE) is largely dependent on the type, orientation and offset arrangement of the baffles employed. In this paper, the thermal-hydraulic characteristics of STHEs with 90°, 120° and 180° offset arrangements of baffles were studied numerically. The study was performed on 19-tube and 31-tube heat exchangers, and also for three shell-side working fluids: air, water and engine oil. The numerical analyses were carried out using the k-ε model with imposed realizability constraint, and were solved with COMSOL Multiphysics. The STHE with 180° had higher pressure drop than other STHEs for all the ranges of mass flow rate. STHE with 120° showed better performance for shell-side heat transfer coefficient at the same pressure drop while STHE with 90° had much higher performance factor at the same mass flow rate. It is concluded that baffle offset arrangements significantly affected the shell and tube heat exchanger performance.